OPTIMASI SUHU DAN pH TERHADAP AKTIVITAS ENZIM ENDOGLUKANASE MENGGUNAKAN RESPONSE SURFACE METHODOLOGY (RSM) - Kusumaningrum, Ambar; Wayan Gunam, Ida Bagus; Mahaputra Wijaya, I Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
This study aims to determine the optimal temperature and pH for the growth of cellulolytic bacterial isolates to produce high cellulase enzyme activity. This study used one potential cellulolytic bacterial isolate B2S8 which had the highest cellulose degradation value and highest cellulase enzyme activity in previous studies. Carboxymethyl Cellulose (CMC) was used as a substrate on growth media and enzyme activity test. Optimization of temperature and pH on cellulase enzyme activity was done by Response Surface Methodology (RSM) by Central Composite Design (CCD). The results using Response Surface Methodology (RSM) showed that the highest endoglucanase enzyme activity was at 36.9 ºC and pH 6.9 was equal to 0.0269 IU/mL. Keywords : cellulolytic bacteria, endoglucanase enzyme, activity, Response Surface Methodology.